(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In order to help achieve the objectives of the heavily stressed idea of inclusion, it is necessary and crucial that teachers receive training in the use of ICT in teaching and learning. In order to ensure that a classroom is truly inclusive, it is crucial for teachers to possess the knowledge and abilities needed to remove frequent learning barriers that appear as a result of individual differences of a cultural, social, physical, psychological, and economic nature. In this article, comparative analysis between government school teacher and private school teacher on integration of ICT in classroom with special focus to Malda District, West Bengal, India has been evaluated.